2018
DOI: 10.1186/s40842-018-0054-7
|View full text |Cite
|
Sign up to set email alerts
|

Graves’ hyperthyroidism in pregnancy: a clinical review

Abstract: BackgroundGraves’ hyperthyroidism affects 0.2% of pregnant women. Establishing the correct diagnosis and effectively managing Graves’ hyperthyroidism in pregnancy remains a challenge for physicians.MainThe goal of this paper is to review the diagnosis and management of Graves’ hyperthyroidism in pregnancy. The paper will discuss preconception counseling, etiologies of hyperthyroidism, thyroid function testing, pregnancy-related complications, maternal management, including thyroid storm, anti-thyroid drugs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
71
0
15

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 88 publications
0
71
0
15
Order By: Relevance
“…This is of significant importance because hyperthyroidism in pregnancy is associated with a range of adverse pregnancy outcomes, including low birth weight, intra‐uterine growth restriction (IUGR), pregnancy‐induced hypertension and pregnancy loss (Carroll & Matfin, ; Ross, 2017; Nguyen et al . ). A number of recent clinical trials have demonstrated that selenium supplementation can reduce thyroid autoimmunity (Mantovani et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is of significant importance because hyperthyroidism in pregnancy is associated with a range of adverse pregnancy outcomes, including low birth weight, intra‐uterine growth restriction (IUGR), pregnancy‐induced hypertension and pregnancy loss (Carroll & Matfin, ; Ross, 2017; Nguyen et al . ). A number of recent clinical trials have demonstrated that selenium supplementation can reduce thyroid autoimmunity (Mantovani et al .…”
Section: Discussionmentioning
confidence: 97%
“…current animal model, we aimed to investigate possible mechanisms linking selenium deficiency to increased thyroid hormone levels. This is of significant importance because hyperthyroidism in pregnancy is associated with a range of adverse pregnancy outcomes, including low birth weight, intra-uterine growth restriction (IUGR), pregnancy-induced hypertension and pregnancy loss (Carroll & Matfin, 2010;Ross, 2017;Nguyen et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These immunoglobulins, IgG type, have two types of possible action: some stimulate the synthesis of Cyclic Adenosine Monophosphate by these cells, these are the thyroid stimulating immunoglobulins (TSI) while other antibodies will block the binding of TSH with its receptor, these are the thyroid binding inhibiting Immunoglobulins (TBII). Among pregnant women with Graves' disease, 0.2% develops clinical hyperthyroidism and, among them, 1 to 5% of their newborns will present a neonatal hyperthyroidism due to transplacental passage of TRAb [2,6]. Indeed, the fetal thyroid starts its synthesis of thyroid hormone from the 12th week of gestation.…”
Section: Physiopathologymentioning
confidence: 99%
“…This explains why fetal hyperthyroidism doesn't appear until the second half of pregnancy, and also in patients with a rate of higher autoantibodies (TRAb) [2,5,[7][8]. The fetal risk concerns both the fetuses of mothers with the past or current Graves' disease and includes: intrauterine growth retardation, prematurity, intrauterine fetal death (15-25% if untreated), fetal Graves' disease [2][3]6]. Moreover the presence of autoantibodies can encourage the development of fetal goiter, responsible in rare cases to a compression of the trachea or fetal esophageal [6].…”
Section: Physiopathologymentioning
confidence: 99%
See 1 more Smart Citation